2017
DOI: 10.1017/s1041610217001831
|View full text |Cite
|
Sign up to set email alerts
|

Falls in hospitalized geriatric psychiatry patients: high incidence, but only a few fractures

Abstract: Fall rates from 3.2 to 17.1 falls per 1,000 hospital days in geriatric psychiatry facilities have been reported to date. Up to 5% of the falls result in severe injuries, but data concerning medical consequences are scare. This brief report presents a retrospective analysis of one year fall protocols from a geriatric psychiatry department focusing on consequences of falls. Fall-induced injuries were rated in four categories: no injuries, mild injuries (contusions, hematomas, abrasions), moderate injuries (lacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…Only 3 studies reported on the consequences of falling. Oepen et al 24 reported on the outcome after a fall, finding that 73.5% of fallers sustained no injury, 13.1% had mild injury, 11.6% had moderate injury, and 1.8% suffered severe injury. Turner et al 4 reported an injurious fall rate of 1.9 injurious falls per 1000 hospital days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 3 studies reported on the consequences of falling. Oepen et al 24 reported on the outcome after a fall, finding that 73.5% of fallers sustained no injury, 13.1% had mild injury, 11.6% had moderate injury, and 1.8% suffered severe injury. Turner et al 4 reported an injurious fall rate of 1.9 injurious falls per 1000 hospital days.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 18 included studies, there were 4 prospective cohort studies, [11][12][13][14] 8 retrospective cohort studies, 10,15-20 3 case-control studies, [21][22][23] and 3 case series. 4,24,25 The oldest study dates back to 1975 while the most recent was published in 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Por ser um evento com características não intencionais, ocorrem em grande parte em populações mais vulneráveis, em especial crianças, idosos e pacientes psiquiátricos. 2 Entre os principais incidentes de segurança no ambiente hospitalar, as quedas se destacam, sendo responsáveis por dois em cada cinco eventos relacionados à assistência do paciente. 3 As instituições públicas e privadas têm aumentado sua preocupação em relação a determinados grupos de pacientes que seriam mais propensos a cair, como os psiquiátricos, em razão da alta taxa de comorbidades e do uso recorrente de medicamentos psicotrópicos.…”
Section: Introductionunclassified
“…Observa-se que iniciativas nacionais e internacionais vêm sendo desenvolvidas para estimular a análise de indicadores e a implantação de políticas e práticas para garantir uma assistência mais segura (5) , bem como auxiliar no planejamento e promoção de ações preventivas ao paciente (6) . Portanto, as quedas representam um indicador de qualidade da assistência prestada nas instituições de saúde, tornando-se uma preocupação para as instituições hospitalares (7) .…”
Section: Introductionunclassified